Menulis Cerita Melalui Peta Pikiran Berbasis Kolokasi Kata - Harsono Harsono; Yanti Linarsih (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2020)
Writing stories is a difficult because of the limited vocabulary of the students. The concept map is one that is considered effective in overcoming this problem. The concept map in question must have innovations in the form of proper collocations so students will be able to write stories intact, cohesive and coherent This study aims to determine the differences in writing stories through the application of learning innovation based on word collocation mind maps with mind maps without word collocations. The population was taken in class III SDI Al Munawwarah Pamekasan. The sample in this study was class III A as many as 20 students with the application of word collocation-based mind map innovation as an experimental class with class III B SDI Al Munawwarah 20 students with mind maps without word collocation as a control class. Data collection using the test method then analyzed using descriptive analysis. The analysis showed a difference in the results of writing a story with a mind map based on collocation of words with excellent indicators of 25% and good indicators of 75%. While the control class with good indicators is 65% and sufficient indicators are 35%